Positive pole piece, preparation method thereof and electrochemical device
During the preparation process of the positive electrode sheet, the pore structure of the positive electrode sheet is reconstructed by using the "non-solvent induction" process of the inducer and the binder, and the problems of low porosity and high tortuity are solved, and the compatibility between high porosity and low tortuity is achieved, and the rate performance of the battery is improved.
Patent Information
- Application Number
- CN202510070722.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-11
AI Technical Summary
When the thickness of the positive electrode sheet is large or the compaction density is large, the porosity is low and the tortuosity is large, resulting in a decrease in the electrolyte infiltration performance and affecting the battery rate performance.
By infiltrating the positive electrode foil in the inducer, the pore structure of the positive electrode sheet is reconstructed by using the "nonsolvent induction" process with the solubility parameter K of the inducer and binder at 10≤K≤22, thereby reducing tortuosity and improving porosity.
The high porosity and low tortuity of the positive electrode sheet are achieved, the wetting performance of the electrolyte is improved, the rate performance of the battery is improved, and it is suitable for positive electrode sheets with larger thickness or higher compaction density.
Smart Images

Figure CN119812341A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of new energy materials, and in particular to a positive electrode sheet, a preparation method thereof, and an electrochemical device. Background Art
[0002] As the demand for higher driving range of electric vehicles continues to grow, it is particularly important to develop lithium-ion battery systems with higher energy density. One way to improve battery energy density is to use thicker positive electrode sheets. This strategy not only increases the energy density of the battery, but also reduces production costs by minimizing the use of battery cell foil.
[0003] However, when the thickness of the positive electrode sheet is large or the compaction density is large, the porosity of the positive electrode sheet is lower and the tortuosity is greater, which reduces the wetting performance of the electrolyte, thereby resulting in a decrease in the rate performance of the prepared battery. Summary of the invention
[0004] In view of this, in order to solve at least one of the above technical problems, an embodiment of the present application provides a method for preparing a positive electrode sheet with high porosity and low tortuosity.
[0005] In addition, the embodiments of the present application also provide a positive electrode sheet manufactured by the aforementioned method for manufacturing a positive electrode sheet and an electrochemical device using the positive electrode sheet.
[0006] The present invention provides a method for preparing a ternary positive electrode material, which comprises the following steps: Mixing a positive electrode material, a conductive agent, a binder and a solvent to obtain a positive electrode slurry; Applying the positive electrode slurry on a current collector to obtain a positive electrode foil; The positive electrode foil is soaked in an inducer and then dried to obtain the positive electrode sheet, wherein the solubility parameter K of the inducer and the binder satisfies 10≤K≤22.
[0007] In some possible embodiments, the infiltration time is 5s to 30s.
[0008] In some possible embodiments, the binder includes at least one of n-butanol, ethanol, methanol and ethylene glycol.
[0009] In some possible embodiments, the positive electrode slurry further contains a pore former.
[0010] In some possible embodiments, the pore-forming agent includes at least one of oxalic acid, ammonium bicarbonate and an organic polymer pore-forming agent; and / or The mass of the pore former is 0.1% to 0.5% of the mass of the positive electrode material.
[0011] In some possible embodiments, the drying temperature is 70°C to 200°C.
[0012] In some possible embodiments, the thickness of the active material in the positive electrode sheet is 100 μm to 200 μm; The compaction density of the positive electrode sheet is 2.10 g / cm 3 ~2.65g / cm 3 ; The porosity of the positive electrode sheet is 15% to 35%; The tortuosity of the positive electrode plate is 2-15.
[0013] In some possible embodiments, the binder includes at least one of polyvinylidene fluoride, carboxymethyl cellulose, polyacrylic acid, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polytetrafluoroethylene, sodium carboxymethyl cellulose and styrene-butadiene rubber; and / or The solvent includes at least one of N-methylpyrrolidone and water.
[0014] The embodiment of the present application also provides a positive electrode sheet, which is prepared by the above-mentioned method for preparing the positive electrode sheet.
[0015] In addition, an embodiment of the present application further provides an electrochemical device, which includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet is the aforementioned positive electrode sheet.
[0016] Compared with the prior art, the preparation method of the positive electrode plate provided in the embodiment of the present application is through the process of soaking the positive electrode foil in the inducer, and the solubility parameter K of the inducer compared with the binder in the positive electrode slurry satisfies: 10≤K≤22, and the solubility of the inducer and the binder is poor, so that the positive electrode slurry and the inducer in the positive electrode foil can undergo a "non-solvent induction" process of mutual exchange, that is, at least part of the binder in the positive electrode slurry flows from the positive electrode slurry to the inducer, and at least part of the inducer enters the positive electrode slurry, so that the binder and the inducer can shuttle in the positive electrode slurry. This "non-solvent induction" process can induce the reconstruction of the pore structure in the positive electrode plate, thereby reducing the tortuosity of the positive electrode plate and increasing the porosity of the positive electrode plate. This application uses the "non-solvent induction" method of infiltrating the positive electrode foil with the above-mentioned inducer to increase the porosity of the positive electrode sheet while reducing the tortuosity of the positive electrode sheet, so that the positive electrode sheet has the characteristics of high porosity and low tortuosity, which is conducive to the infiltration of the electrolyte into the positive electrode sheet and effectively improves the rate performance of the prepared battery. The preparation method of the positive electrode sheet can be applied to thicker or higher compaction density positive electrode sheets, thereby taking into account the requirements of high energy density and high rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 A process flow chart of a method for preparing a positive electrode plate provided in an embodiment of the present application. DETAILED DESCRIPTION
[0018] The embodiments of the present application are described in detail below. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application.
[0019] It should be noted that, unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the implementation methods of this application and the features in the implementation methods can be combined with each other unless there is a conflict; many specific details are elaborated in the following description to facilitate a full understanding of this application, and the described implementation methods are only part of the implementation methods of this application, rather than all of the implementation methods.
[0020] See also Figure 1 As shown, the embodiment of the present application provides a method for preparing a positive electrode sheet, which specifically includes the following steps: Step S1, mixing a positive electrode material, a conductive agent, a binder and a solvent to obtain a positive electrode slurry.
[0021] Specifically, the positive electrode material, the conductive agent, the binder and the solvent are mixed evenly in a stirring tank to obtain a positive electrode slurry. The mixing condition can be a vacuum, which can effectively eliminate bubbles in the positive electrode slurry and facilitate the subsequent uniform coating of the positive electrode slurry on the surface of the current collector. The mixing temperature can be 25°C to 30°C, which is conducive to further adjusting the viscosity of the positive electrode slurry.
[0022] In some embodiments, the positive electrode material may include but is not limited to at least one of lithium iron phosphate (LFP), lithium iron manganese phosphate (LMFP), lithium cobalt oxide (LCO), nickel cobalt manganese ternary positive electrode material (NCM), and nickel cobalt aluminum ternary positive electrode material (NCA).
[0023] In some embodiments, the conductive agent may include but is not limited to at least one of conductive carbon black (SP) and carbon nanotubes (CNT), etc. The above conductive agents can enhance the conductivity of the positive electrode sheet.
[0024] In some embodiments, the binder may include but is not limited to at least one of polyvinylidene fluoride (PVDF), carboxymethyl cellulose (CMC), polyacrylic acid (PAA), polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polytetrafluoroethylene, sodium carboxymethyl cellulose, and styrene-butadiene rubber.
[0025] In some embodiments, the solvent may include but is not limited to at least one of N-methylpyrrolidone (NMP) and water, etc. The solvent is used to dissolve the binder, which is beneficial to adjust the solid content and viscosity of the positive electrode slurry and facilitate the coating of the positive electrode slurry on the current collector.
[0026] In some embodiments, the mass ratio of the positive electrode material, the conductive agent and the binder in the positive electrode slurry can be (95.5~97.5): (1.0~2.1): (2.4~1.5), which is beneficial to provide good electrochemical activity, conductivity, stability and mechanical strength for the positive electrode sheet.
[0027] In some embodiments, the solid content of the positive electrode slurry can be 64.0%~69.0%. By adjusting the solid content of the positive electrode slurry within the above range, the viscosity and energy density of the positive electrode slurry can be balanced, so that the positive electrode slurry is more uniform during coating, effectively improving the uniformity, electrochemical performance and structural stability of the positive electrode sheet.
[0028] Step S2, coating the positive electrode slurry on the current collector to obtain a positive electrode foil.
[0029] In some embodiments, the coating surface density can be 320 g / m 2 ~380g / m 2 The coating surface density will have a certain impact on the thickness and compaction density of the final positive electrode sheet. The coating surface density in the above range can provide higher capacity and energy density. The coating surface density can further be 350g / m 2 ~380g / m 2 , which is beneficial to increase the capacity of the positive electrode sheet and the energy density of the electrochemical device. The coating surface density can be 320g / m 2 , 330g / m 2 , 340g / m 2 , 350g / m 2 , 360g / m 2 , 370g / m 2 , 380g / m 2 Or any value within the numerical range formed by any two of the above values.
[0030] Step S3, soaking the positive electrode foil in the inducer and then drying to obtain a positive electrode sheet, wherein the solubility parameter K of the inducer relative to the binder satisfies: 10≤K≤22.
[0031] Specifically, the positive electrode foil coated with the positive electrode slurry is placed in an inductor for infiltration, and then the positive electrode foil is taken out for drying to obtain a positive electrode sheet, wherein the solubility parameter K of the inductor relative to the binder in the positive electrode slurry ranges from 10 to 22. After drying, the positive electrode sheet is mainly composed of a current collector and an active material layer (composed of a positive electrode active material, a conductive agent, a binder, etc.), and the active material layer forms a thin film on the surface of the current collector, and completes the charge and discharge function of the prepared battery by combining with the current collector.
[0032] The solubility parameter K is an important parameter to describe the compatibility of substances. K=4 (δd 诱导剂 -δd 粘结剂 ) 2 +(δp 诱导剂 -δp 粘结剂 ) 2 +(δh 诱导剂 -δh 粘结剂 ) 2 , the solubility parameter K is evaluated based on the comprehensive differences in the dispersion parameter (δd), polarity parameter (δp) and hydrogen bonding parameter (δh) between the two substances. The inducer used in the embodiment of the present application has a solubility parameter K of 10~22 relative to the binder in the positive electrode slurry, indicating that the inducer and the binder have poor solubility. Therefore, the positive electrode slurry and the inducer in the positive electrode foil will undergo a "non-solvent induction" process of mutual exchange, that is, at least part of the binder in the positive electrode slurry flows from the positive electrode slurry to the inducer, and at least part of the inducer enters the positive electrode slurry. The shuttle between the binder and the inducer in the positive electrode slurry can induce the reconstruction of the pore structure of the positive electrode sheet. The reconstruction of the material pore structure caused by this "non-solvent induction" process can effectively improve the porosity of the positive electrode sheet, while also reducing the tortuosity of the positive electrode sheet.
[0033] In the positive electrode sheet, the increase in porosity is conducive to improving the permeability of the electrolyte, increasing the charge and discharge rate, and thus improving the rate performance of the positive electrode sheet. The reduction in tortuosity means that the surface of the positive electrode sheet is smoother, which is conducive to full contact between the positive electrode sheet and the electrolyte, improving the electrolyte permeability and the transmission efficiency of lithium ions, and reducing the internal resistance, thereby further improving the rate performance of the positive electrode sheet. In particular, in order to increase the capacity, it is necessary to design a thicker and / or more compacted positive electrode sheet. The method of the embodiment of the present application can achieve compatibility of high porosity and low tortuosity of the positive electrode sheet.
[0034] The solubility parameter K of the inducer relative to the binder will also affect the flexibility of the positive electrode sheet. When K is 10~22, the positive electrode sheet has good flexibility and ductility. When the K value is too large (K>22), it is easy to increase the brittleness of the positive electrode sheet, and it is difficult to meet the requirements of the processing performance of the positive electrode sheet; when the K value is too small (K<10), the inducer and the binder are more compatible, and it is difficult to perform "non-solvent induction" on the positive electrode sheet to achieve pore structure reconstruction, and the improvement effect on the porosity and tortuosity of the positive electrode sheet is not good.
[0035] According to the solubility parameter K of the inducer relative to the binder being 10-22, the binder can be selected from PVDF, and the inducer can be selected from at least one of n-butanol, ethanol, methanol and ethylene glycol. When the solubility parameter K of the inducer and PVDF is in the range of 10-22, the inducer can effectively enter the positive electrode slurry and PVDF can flow to the surface of the positive electrode slurry and enter the inducer, realizing the "non-solvent induction" process, thereby reconstructing the pore structure of the positive electrode sheet, increasing the porosity of the positive electrode sheet while reducing the tortuosity.
[0036] In other embodiments, the binder may also include at least one of traditional additives in the lithium battery industry, such as polyvinylidene fluoride, carboxymethyl cellulose, polyacrylic acid, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polytetrafluoroethylene, sodium carboxymethyl cellulose, and styrene-butadiene rubber. It is understandable that the combination of the inducer and the binder includes but is not limited to the above examples, and the selection of the inducer can be changed according to the different binders, as long as the solubility parameter K of the inducer and the binder is in the range of 10 to 22.
[0037] In addition, the infiltration time of the positive electrode foil in the inducer will also affect the effect of "non-solvent induction". The infiltration time within the above range is conducive to full infiltration and maintaining a good appearance structure. Specifically, the embodiment of the present application can achieve full infiltration of the inducer and the positive electrode foil by controlling the infiltration time to 5s~30s. The infiltration time can further be 10s~20s, and can be illustratively 5s, 8s, 10s, 12s, 15s, 18s, 20s, 22s, 25s, 28s, 30s or any value within the numerical range composed of any two of the above values.
[0038] In some embodiments, the drying temperature may be 70°C to 200°C. By controlling the drying temperature within the aforementioned range, volatile substances such as the inducing agent can be fully removed, and the residual excess components in the positive electrode sheet can be reduced. The drying temperature may further be 80°C to 150°C, and may be 70°C, 90°C, 100°C, 110°C, 120°C, 130°C, 150°C, 170°C, 190°C, 200°C or any value within the numerical range consisting of any two of the above values.
[0039] In some embodiments, the porosity of the positive electrode sheet may be 15% to 35%. The positive electrode sheet prepared in the embodiment of the present application has a porosity of 15% to 35%, which is conducive to good infiltration with the electrolyte. The porosity of the positive electrode sheet may further be 20% to 35%, and may be 15%, 18%, 20%, 22%, 25%, 28%, 30%, 33%, 35% or any value within the numerical range composed of any two of the above values.
[0040] In some embodiments, the tortuosity of the positive electrode sheet can be 2-15. The positive electrode sheet prepared in the embodiment of the present application has a tortuosity of 2-15, which is beneficial to reduce the internal resistance of the positive electrode sheet and to make the contact interface between the positive electrode sheet and the electrolyte more uniform and stable. The tortuosity of the positive electrode sheet can further be 3-10, and can be exemplarily 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15 or any value within the numerical range composed of any two of the above values.
[0041] In order to further control the porosity of the positive electrode sheet, in the aforementioned step S1, a pore former may be added to the positive electrode slurry. By adding the pore former, a controllable pore structure can be introduced during the preparation of the positive electrode sheet, thereby further improving the porosity of the positive electrode sheet.
[0042] In some embodiments, the pore former may include at least one of oxalic acid, ammonium bicarbonate, and organic polymer pore formers, etc. The above pore formers can undergo sublimation and / or thermal decomposition reactions at a certain temperature, which is conducive to the formation of pores.
[0043] In some embodiments, the mass of the pore former can be 0.1% to 0.5% of the mass of the positive electrode material in the positive electrode slurry. Adjusting the addition ratio of the pore former within the above range is conducive to further optimizing the porosity of the prepared positive electrode sheet. The mass of the pore former can further be 0.2% to 0.4% of the mass of the positive electrode material in the positive electrode slurry, and can be 0.1%, 0.15%, 0.18%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5% or any value within the numerical range composed of any two of the above values.
[0044] In some embodiments, the positive electrode material, the conductive agent, the binder, the pore former and the solvent may be mixed in a step-by-step manner, wherein the positive electrode active material, the conductive agent and the binder are first mixed evenly, and then part of the solvent is added and stirred, and then the pore former is added and stirred continuously, and the remaining part of the solvent is added to adjust the solid content of the positive electrode slurry, and the positive electrode slurry is stirred continuously until the positive electrode slurry is mixed evenly. This step-by-step mixing method is conducive to the full mixing and dispersion of the positive electrode slurry. It is understandable that the mixing method includes but is not limited to the above method, and any method that can achieve the mixing of the positive electrode slurry is acceptable.
[0045] When the positive electrode slurry contains a pore former, the drying process is not only beneficial to the removal of volatile substances such as the inducer and the reduction of excess residual components in the positive electrode sheet, but also needs to consider the volatilization or decomposition of the pore former. The drying temperature needs to make the pore former, the decomposition product of the pore former or a mixture of the two in the positive electrode slurry be released from the inside to the outside of the positive electrode slurry, and a large number of pore structures are formed in the positive electrode sheet, which synergizes with the inducer to further improve the porosity of the positive electrode sheet while maintaining a low tortuosity.
[0046] Further, the drying temperature can be 70°C to 200°C, which is conducive to the sublimation and thermal decomposition of the pore-forming agent, and accelerates the release of the pore-forming agent, the decomposition product of the pore-forming agent, or a mixture of the two. The drying temperature can further be 80°C to 150°C, and can be illustratively 70°C, 90°C, 100°C, 110°C, 120°C, 130°C, 150°C, 170°C, 190°C, 200°C, or any value within the numerical range composed of any two of the above values.
[0047] Illustratively, when the pore-forming agent is oxalic acid, oxalic acid begins to sublime when the drying temperature is about 80°C to 100°C, and sublimates rapidly when the drying temperature is about 110°C to 130°C. Oxalic acid sublimates from the positive electrode slurry to bring a large number of tiny pores to the positive electrode sheet, which can improve the porosity of the positive electrode sheet. When the drying temperature is above 150°C, oxalic acid will decompose by heat to produce CO2 and H2O. Oxalic acid and its decomposition products will be released from the inside of the positive electrode sheet slurry to the outside. During this release process, many pore structures will also be formed inside the positive electrode sheet, and the porosity of the positive electrode sheet will be improved.
[0048] In some embodiments, the compaction density of the positive electrode sheet can be 2.1 g / cm 3 ~2.65g / cm 3 At the same electrode thickness, a higher compaction density is beneficial to reducing the internal resistance of the positive electrode and improving the energy density of the positive electrode. The compaction density of the positive electrode can be further 2.3g / cm 3 ~2.6g / cm 3 , which can be 2.1 g / cm 3 , 2.15g / cm 3, 2.2g / cm 3 , 2.25g / cm 3 , 2.3g / cm 3 , 2.35g / cm 3 , 2.4g / cm 3 , 2.45g / cm 3 , 2.5g / cm 3 , 2.55g / cm 3 , 2.6g / cm 3 , 2.65g / cm 3 Or any value within the numerical range formed by any two of the above values.
[0049] In some embodiments, the thickness of the active material in the positive electrode sheet (i.e., the thickness of the active material layer formed by the positive electrode slurry coated only without the current collector in the positive electrode sheet after the steps of infiltration, drying, etc.) can be 100μm~200μm, and the thickness of the active material is related to the coating surface density and the compaction density of the positive electrode sheet. At the same compaction density, the greater the coating surface density, the greater the thickness of the active material layer. A thicker active material layer is conducive to increasing the capacity of the positive electrode sheet and increasing the energy density of the electrochemical device. The thickness of the active material layer can further be 150μm~200μm, and can be exemplarily 100μm, 110μm, 120μm, 130μm, 140μm, 150μm, 160μm, 170μm, 180μm, 190μm, 200μm or any value within the numerical range composed of any two of the above values.
[0050] Compared with the prior art, the method for preparing the positive electrode sheet provided in the embodiment of the present application has the following beneficial effects: 1. The positive electrode foil is infiltrated with an inducer whose solubility parameter K satisfies 10≤K≤22 with the binder. The inducer and the positive electrode slurry are "non-solvent induced" to shuttle the binder and the inducer in the positive electrode slurry, thereby reconstructing the pore structure of the positive electrode sheet, reducing the tortuosity of the positive electrode sheet, and forming a large number of pores to increase the porosity of the positive electrode sheet. The increase in the porosity of the positive electrode sheet and the reduction in tortuosity are conducive to improving the wetting effect between the positive electrode sheet and the electrolyte, reducing the resistance of the positive electrode sheet, and improving the rate performance of the positive electrode sheet.
[0051] 2. By adding a pore former to the positive electrode slurry, the pore former and / or the decomposition product of the pore former is released from the inside of the positive electrode slurry to the outside of the positive electrode slurry to form a large number of pore structures, further improving the porosity of the positive electrode sheet and improving the rate performance of the positive electrode sheet. The addition of a pore former can work synergistically with the inducer to further improve the porosity of the positive electrode sheet while maintaining a low tortuosity.
[0052] 3. The preparation method is simple and efficient, and will not cause structural damage to the positive electrode sheet. It can also be applied to positive electrode sheets with larger thickness or higher compaction density, which is conducive to the large-scale production of positive electrode sheets and has excellent commercial prospects.
[0053] The embodiment of the present application also provides a positive electrode sheet, which is prepared by the above-mentioned preparation method of the positive electrode sheet. Compared with the prior art, the positive electrode sheet has a higher porosity and a lower tortuosity, so that the electrolyte can effectively infiltrate the positive electrode sheet, reduce the resistance of the positive electrode sheet, and improve the rate performance of the positive electrode sheet. When the thickness of the positive electrode sheet is increased to increase the capacity or the compaction density of the positive electrode sheet is increased to increase the energy density, the positive electrode sheet can still maintain good rate performance.
[0054] The present application also provides an electrochemical device (such as a battery), which includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet is the positive electrode sheet as described above. The electrochemical device prepared using the positive electrode sheet has the advantages of high energy density and high rate performance.
[0055] The above-mentioned positive electrode sheet and its preparation method and electrochemical device are further described below through specific examples.
[0056] Example 1 Step 1: After LFP, SP, CNT and PVDF are evenly mixed, a certain amount of NMP solvent is added, and the mixture is stirred for 2-3 hours. The solid content of the slurry is adjusted to 64.0%~69.0% with NMP solvent, and high-speed dispersion is continued for 2-3 hours, followed by low-speed dispersion to obtain a positive electrode slurry, wherein the mass ratio of LFP, SP, CNT and PVDF is 96.0:1.2:0.6:2.2.
[0057] Step 2: Apply the above positive electrode slurry on the carbon-coated aluminum foil, and the surface density of the coating is 352.524 g / m 2 , and obtain the positive electrode foil.
[0058] Step 3: Place the positive electrode foil coated with the positive electrode slurry in an ethanol induction agent for 15 seconds, then take out the positive electrode foil for drying at a temperature of 100°C, and roll to obtain a positive electrode sheet. The compaction density of the positive electrode sheet is 2.32 g / cm 3 The thickness of the active material of the positive electrode sheet is 150μm.
[0059] Example 2 Step 1: After LFP, SP, CNT and PVDF are evenly mixed, a certain amount of NMP solvent is added, and the mixture is stirred for 2-3 hours. Then, oxalic acid as a pore-forming agent is added, and the mixture is stirred for 2-3 hours. The solid content of the slurry is adjusted to 64.0%~69.0% with NMP solvent, and the mixture is dispersed at a high speed for 2-3 hours, and then dispersed at a low speed to obtain a positive electrode slurry, wherein the mass ratio of LFP, SP, CNT and PVDF is 96.0:1.2:0.6:2.2, and the amount of oxalic acid added is 0.5wt% of LFP.
[0060] Step 2: Apply the above positive electrode slurry on the carbon-coated aluminum foil, and the surface density of the coating is 352.524 g / m 2 , and obtain the positive electrode foil.
[0061] Step 3: Place the positive electrode foil coated with the positive electrode slurry in an ethanol induction agent for 15 seconds, then take out the positive electrode foil for drying at a temperature of 100°C, and roll to obtain a positive electrode sheet. The compaction density of the positive electrode sheet is 2.32 g / cm 3 The thickness of the active material of the positive electrode sheet is 150μm.
[0062] Example 3 The difference between Example 3 and Example 2 is that in step 1, the amount of oxalic acid added is 0.3wt% of LFP. The preparation method of the remaining positive electrode sheets is basically the same as that of Example 2, and will not be described in detail here.
[0063] Example 4 The difference between Example 4 and Example 2 is that in step 1, the amount of oxalic acid added is 0.1wt% of LFP. The preparation method of the remaining positive electrode sheets is basically the same as that of Example 2, and will not be described in detail here.
[0064] Example 5 The difference between Example 5 and Example 3 is that in step 3, the infiltration time of the inducer is 5 seconds. The preparation method of the remaining positive electrode sheets is basically the same as that of Example 3, and will not be described in detail here.
[0065] Example 6 The difference between Example 6 and Example 3 is that in step 3, the infiltration time of the inducer is 30 seconds. The preparation method of the remaining positive electrode sheets is basically the same as that of Example 3, and will not be described in detail here.
[0066] Example 7 The difference between Example 7 and Example 3 is that in step 3, the inducing agent is n-butanol. The preparation method of the remaining positive electrode sheets is basically the same as that of Example 3, and will not be described in detail here.
[0067] Example 8 The difference between Example 8 and Example 3 is that in step 3, the inducing agent is methanol. The preparation method of the remaining positive electrode sheets is basically the same as that of Example 3, and will not be described in detail here.
[0068] Example 9 The difference between Example 9 and Example 3 is that in step 3, the inducer is ethylene glycol. The preparation method of the remaining positive electrode sheets is basically the same as that of Example 3, and will not be described in detail here.
[0069] Example 10 The difference between Example 10 and Example 3 is that in step 3, the inducer is a mixed solution of methanol and ethanol in a mass ratio of 1:1. The preparation method of the remaining positive electrode sheets is basically the same as that of Example 3, and will not be described in detail here.
[0070] Embodiment 11 The difference between Example 11 and Example 3 is that in step 2, the surface density of the coating is 355.563 g / m 2 The final compaction density of the positive electrode sheet is 2.34g / cm 3 , the thickness of the active material of the positive electrode sheet is 150 μm. The preparation method of the remaining positive electrode sheets is basically the same as that of Example 3, and will not be described in detail here.
[0071] Example 12 The difference between Example 12 and Example 3 is that in step 2, the surface density of the coating is 358.602 g / m 2 The final compaction density of the positive electrode sheet is 2.36g / cm 3 , the thickness of the active material of the positive electrode sheet is 150 μm. The preparation method of the remaining positive electrode sheets is basically the same as that of Example 3, and will not be described in detail here.
[0072] Example 13 The difference between Example 13 and Example 3 is that in step 2, the surface density of the coating is 399.5272 g / m 2 The final compaction density of the positive electrode sheet is 2.32g / cm 3 , the thickness of the active material of the positive electrode sheet is 170 μm. The preparation method of the remaining positive electrode sheets is basically the same as that of Example 3, and will not be described in detail here.
[0073] Comparative Example 1 Step 1: After LFP, SP, CNT and PVDF are evenly mixed, a certain amount of NMP solvent is added, and the mixture is stirred for 2-3 hours. The solid content of the slurry is adjusted to 64.0%~69.0% with NMP solvent, and high-speed dispersion is continued for 2-3 hours, followed by low-speed dispersion to obtain a positive electrode slurry, wherein the mass ratio of LFP, SP, CNT and PVDF is 96.0:1.2:0.6:2.2.
[0074] Step 2: Apply the above positive electrode slurry on the carbon-coated aluminum foil, and the surface density of the coating is 352.524 g / m 2 , and obtain the positive electrode foil.
[0075] Step 3: Dry the positive electrode foil coated with the positive electrode slurry to obtain a positive electrode sheet. The compaction density of the positive electrode sheet is 2.32 g / cm 3 The thickness of the active material of the positive electrode sheet is 150μm.
[0076] Comparative Example 2 Step 1: After LFP, SP, CNT and PVDF are evenly mixed, a certain amount of NMP solvent is added, and the mixture is stirred for 2-3 hours. Then, oxalic acid as a pore-forming agent is added, and the mixture is stirred for 2-3 hours. The solid content of the slurry is adjusted to 64.0%~69.0% with NMP solvent, and the mixture is dispersed at a high speed for 2-3 hours, and then dispersed at a low speed to obtain a positive electrode slurry, wherein the mass ratio of LFP, SP, CNT and PVDF is 96.0:1.2:0.6:2.2, and the amount of oxalic acid added is 0.5wt% of LFP.
[0077] Step 2: Apply the above positive electrode slurry on the carbon-coated aluminum foil, and the surface density of the coating is 352.524 g / m 2 , and obtain the positive electrode foil.
[0078] Step 3: Dry the positive electrode foil coated with the positive electrode slurry to obtain a positive electrode sheet. The compaction density of the positive electrode sheet is 2.32 g / cm 3 The thickness of the active material of the positive electrode sheet is 150μm.
[0079] The performance parameters of the inducer are shown in Table 1, and the relevant parameters of the positive electrode sheets prepared in Examples 1-13 and Comparative Examples 1-2 are shown in Table 2.
[0080] The positive electrode sheets obtained in Examples 1-13 and Comparative Examples 1-2 were prepared into electrochemical devices, and the following performance tests were performed on the positive electrode sheets and the electrochemical devices.
[0081] (1) Pole piece porosity test: Cut the pole piece to be tested into square samples with certain length and width. Measure and calculate the apparent volume V1 of the sample, V1=S×d (where S is the pole piece area, in cm 2; d is the thickness of the pole piece, in cm). AccuPyc 1340 true density instrument was used, referring to the porosity test method in GB / T24586-2009, using the helium displacement method, combined with Archimedes principle and Bohr's law (PV=nRT), to accurately measure the true volume V2 of the material being tested, in cm 3 The total porosity of the electrode is calculated by the formula Q = (V1-V2) / V1×100%, and the results are shown in Table 3.
[0082] (2) Tortuosity test: Calculation of the tortuosity (P) of the positive electrode sheet: P = L / L1, L = 2 × PD × Dv99 × (1-Q), where L represents the shortest path for active ions (lithium ions) to be transported in the active material layer, L1 represents the thickness of the active material layer in μm, and PD represents the compaction density of the positive active material layer in g / cm 3 , Dv99 represents the particle size corresponding to when the cumulative volume distribution percentage of the positive electrode active material particles reaches 99%, and the unit is μm. Q represents the porosity of the positive electrode active material layer, and Q represents the porosity of the positive electrode active material layer. The results are shown in Table 3.
[0083] (3) Electrode liquid retention test: The prepared positive electrode is rolled and cut into 2 cm × 2 cm square samples. The weight of the electrode is recorded as M1. The sample is immersed in the electrolyte for 30 s. The electrode is fished out and the weight of the electrode is recorded as M2. The liquid absorption of the electrode electrolyte is M = (M2-M1) / M1×100%. The solvent of the electrolyte is ethylene carbonate: diethyl carbonate: dimethyl carbonate = 2:5:3 (mass ratio). The lithium salt is 1 mol / L LiPF6. The additive is 2% by mass of vinyl carbonate. The results are shown in Table 3.
[0084] (4) Pole sheet resistance test: The test instrument is a GDW3-KDY-2 two-probe diaphragm resistance tester (Beijing Zhonghui Tiancheng Technology). Take the positive electrode sheet to be tested and prepare a 4cm×25cm sample. Dry the sample at 85℃ under vacuum for more than 4 hours, and the test pressure is 0.2~0.4Mpa. The results are shown in Table 4.
[0085] (5) Assemble the positive electrode sheet into an electrochemical device: Prepare the negative electrode sheet: Mix graphite, SP, styrene butadiene rubber, and sodium carboxymethyl cellulose in a mass ratio of 96.1:0.8:0.6:2.5, add an appropriate amount of deionized water, control the solid content to 54.0%~56.0%, stir for 2~3h, then add 60% of the total mass of the above materials as binder styrene butadiene rubber and NMP, adjust the slurry viscosity and solid content, control the solid content to 49.0%~51.0%, disperse at a low speed for 0.5~1.0h, maintain a vacuum state during stirring, and use condensed water to cool down to obtain the negative electrode slurry. The negative electrode slurry is coated on copper foil, and the capacity ratio of the negative electrode to the positive electrode (NP ratio) is controlled at 1.13~1.17. The negative electrode sheet does not need to be wetted, and is directly dried to obtain the negative electrode sheet. The compaction density of the negative electrode sheet is 1.43g / cm 3 After striping and die-cutting, the processes of lamination, assembly, cell baking, liquid injection, formation, and capacity division (capacity division ratio is 0.3C) are completed in sequence to obtain an aluminum shell battery with a rated capacity of 100Ah.
[0086] Measuring the rate performance of the electrochemical device: Under 25°C oven conditions, the battery with SOC=0% (2.0V) state of charge was charged at 0.33C to SOC=100% (3.65V), and then discharged at 0.33C to 2.0V. The discharge capacity at this time was recorded as C1. For the same battery, under the same test conditions, the battery with SOC=0% (2.0V) state of charge was charged at 0.33C to SOC=100% (3.65V), and then discharged at 2C to 2.0V. The discharge capacity at this time was recorded as C2. The test index of the discharge rate performance is capacity retention rate = C2 / C1×100%, and the results are shown in Table 4.
[0087] The above results show: Combined with Table 2 and Table 3, compared with Comparative Example 1 (without infiltration with inducer and addition of pore-forming agent), under the action of inducer, the tortuosity of the positive electrode sheet of Example 1 was reduced by 3.86, and the porosity of the positive electrode sheet was also increased by 4%; compared with Comparative Example 2 (only adding pore-forming agent), although the porosity of Comparative Example 2 was significantly improved due to the addition of pore-forming agent, it caused the tortuosity to increase, which was not conducive to electrolyte infiltration (the electrolyte absorption of Comparative Example 2 was only 16.21%), while the porosity and tortuosity of Example 1 were improved, and the electrolyte absorption was increased to 18.21%. Due to the co-infiltration effect of the inducer on the surface of the positive electrode sheet, the inducer infiltrated along the surface of the positive electrode sheet toward the foil area, reducing the tortuosity of the sheet while bringing more porosity to the positive electrode sheet. By comparing Examples 2-4, it is found that under the use of the inducer ethanol, the addition of a pore-forming agent can further improve the porosity of the positive electrode material. When the amount of the pore-forming agent added is 0.1% (Example 4) and the porosity of the electrode sheet is significantly improved by about 10%, the positive electrode sheet has a higher porosity and the tortuosity is reduced. The increase in the porosity of the positive electrode sheet and the reduction in the tortuosity effectively increase the liquid absorption rate of the positive electrode sheet, enabling the positive electrode sheet to absorb more electrolyte per unit time. By comparing Examples 3, 5 and 6, it is found that the infiltration of the inducer has a unique advantage in reducing the tortuosity of the electrode sheet. The tortuosity of the positive electrode sheet has been significantly reduced after the electrode sheet has been infiltrated with the inducer for more than 5s. In addition, by comparing Examples 3 and 7-10, it is found that different inducers with solubility parameters K of 10~22 in this application have improved the tortuosity of the positive electrode sheet. By comparing Examples 3 and 11-13, it is found that even if the compaction density of the positive electrode material is increased from 2.32g / cm 3 Increased to 2.34g / cm 3 and 2.36 g / cm 3 , and the thickness of the positive electrode material is increased from 150μm to 170μm, the porosity and tortuosity of the positive electrode sheet are still well improved. The preparation method of the positive electrode sheet of the present application brings huge application potential for the development of positive electrode sheets with higher compaction density or thicker positive electrode sheets.
[0088] Combining Table 2 and Table 4, compared with Comparative Examples 1-2, due to the effect of the inducer, the positive electrode sheet resistance of Example 1 is reduced, and the corresponding discharge rate performance is also increased. The sheet resistance of Comparative Example 2 is higher than that of Comparative Example 1, indicating that the increase in the porosity of a single positive electrode sheet has no effect on the sheet resistance of the positive electrode sheet, but will hinder the Li +In the migration rate of the positive electrode sheet, even if the amount of electrolyte absorbed by the positive electrode sheet increases, the discharge rate performance of the assembled battery cell is not well improved. In Examples 3 and 7 of the present application, under the coordinated action of the pore former and the inducer, a positive electrode sheet with high porosity and low tortuosity is prepared, the positive electrode sheet has a lower membrane resistance, and the discharge rate performance is also improved by about 3% compared with Comparative Example 1.
[0089] It is to be understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of the present invention, but the present invention is not limited thereto. For those of ordinary skill in the art, various modifications and improvements can be made without departing from the spirit and essence of the present invention, and these modifications and improvements are also considered to be within the scope of protection of the present invention.
Claims
1. A method for preparing a positive electrode sheet, characterized in that: include: Mixing a positive electrode material, a conductive agent, a binder and a solvent to obtain a positive electrode slurry; Applying the positive electrode slurry on a current collector to obtain a positive electrode foil; and The positive electrode foil is soaked in an inducer and then dried to obtain the positive electrode sheet, wherein the solubility parameter K of the inducer relative to the binder satisfies: 10≤K≤22.
2. The method for preparing a positive electrode sheet according to claim 1, characterized in that: The infiltration time is 5s to 30s.
3. The method for preparing a positive electrode sheet according to claim 1, characterized in that: The inducer includes at least one of n-butanol, ethanol, methanol and ethylene glycol.
4. The method for preparing a positive electrode sheet according to claim 1, characterized in that: The positive electrode slurry also contains a pore former.
5. The method for preparing a positive electrode sheet according to claim 4, characterized in that: The pore-forming agent includes at least one of oxalic acid, ammonium bicarbonate and an organic polymer pore-forming agent; and / or The mass of the pore former is 0.1% to 0.5% of the mass of the positive electrode material.
6. The method for preparing a positive electrode sheet according to claim 1, characterized in that: The drying temperature is 70°C to 200°C.
7. The method for preparing a positive electrode sheet according to claim 1, characterized in that: The thickness of the active material in the positive electrode sheet is 100 μm to 200 μm; The compaction density of the positive electrode sheet is 2.10 g / cm 3 ~2.65g / cm 3 ; The porosity of the positive electrode sheet is 15% to 35%; The tortuosity of the positive electrode plate is 2-15.
8. The method for preparing a positive electrode sheet according to claim 1, characterized in that: The binder comprises at least one of polyvinylidene fluoride, carboxymethyl cellulose, polyacrylic acid, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polytetrafluoroethylene, sodium carboxymethyl cellulose and styrene-butadiene rubber; and / or The solvent includes at least one of N-methylpyrrolidone and water.
9. A positive electrode sheet, characterized in that: The positive electrode sheet is prepared by the method for preparing a positive electrode sheet according to any one of claims 1 to 8.
10. An electrochemical device, characterized in that: The electrochemical device comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet is the positive electrode sheet as claimed in claim 9.
Citation Information
Cited By
Secondary battery, preparation method of secondary battery and power utilization device
CN121097086A